2015
DOI: 10.1371/journal.pone.0138887
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital as a Determinant of Pregnant Mother’s Place of Delivery: Experience from Kongwa District in Central Tanzania

Abstract: IntroductionMaternal ill health contributes highly to the global burden of diseases in countries South of Sahara including Tanzania. Ensuring that all deliveries take place in health facilities and hence attended by skilled health personnel is one of the strategies advocated by global and national policies, including the Millennium Development Goals (MDGs). However, the number of women delivered by skilled health personnel has remained low in sub Saharan Africa despite of a number of interventions. We sought t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Social capital plays an important role in people’s ability to access healthcare services, and as consequence, their health [13]. In pregnancy, higher social capital may increase access to maternity care and facilitate healthy pregnancy [14, 15]. Although the goals of prenatal care may vary according to context and service provider, a woman’s individual factors should also be considered [16].…”
Section: Introductionmentioning
confidence: 99%
“…Social capital plays an important role in people’s ability to access healthcare services, and as consequence, their health [13]. In pregnancy, higher social capital may increase access to maternity care and facilitate healthy pregnancy [14, 15]. Although the goals of prenatal care may vary according to context and service provider, a woman’s individual factors should also be considered [16].…”
Section: Introductionmentioning
confidence: 99%
“…Of the six quantitative cross-sectional studies, ve [24,38,40,45,46] were rated as moderate quality and one [39] was rated high quality. Four out of six studies undertook systematic random sampling in selecting their study participants.…”
Section: Resultsmentioning
confidence: 99%
“…Despite studies in India [24,38], Tanzania [39] and Cameroon [40] countries indicated the role of SC in improving uptake of maternal and child health services, some other studies have identi ed its negative consequences as exclusion of outsiders, excess claims on group members, restrictions on individual freedoms, and downward leveling norms [41,42]. To date, there is no study that systematically synthesizes the available literature focusing on social capital's role to improve maternal and child health services use in LMICs.…”
mentioning
confidence: 99%
“…However, there are some studies from LMICs, where socio-economic inequality is higher, reported that social capital has a stronger relationship and a greater effect on health [ 35 , 36 ]. Our preliminary cursory searches identified additional studies conducted in India [ 27 , 37 ], Tanzania [ 38 ] and Cameroon [ 39 ]. In other African countries such as Ethiopia, there is high levels of group membership, high participation in citizenship activities and high levels of cognitive social capital [ 40 ].…”
Section: Introductionmentioning
confidence: 99%